A coordinated control of hybrid ac/dc microgrids with PV-wind-battery under variable generation and load conditions. (January 2019) - Hu, Jiefeng; Shan, Yinghao; Xu, Yinliang; Guerrero, Josep M.
Highlights: A model predictive power and voltage control of microgrid. The controller is simpler and control parameters tuning free. An energy management scheme to ensure power balance and stable operation. Abstract: Traditional power generation and consumption are undergoing major transformation. One of the tendencies is to integrate microgrids into the distribution network with high penetration of renewable energy resources. This paper proposes a coordinated control strategy for a microgrid with hybrid energy resources and ac/dc loads. First, a local-level coordinated control strategy of distributed converters is presented, where a model predictive power and voltage control (MPPVC) method is developed for the ac/dc interlinking converter to provide high quality voltages and to ensure smooth power transfer between the dc and ac subgrids. Meanwhile, smooth grid synchronization and connection can be achieved. After that, a system-level energy management scheme (EMS) is adopted to ensure stable operation under variable power generation and consumption conditions. Simulation studies based on a 3.5 MW system demonstrate the effectiveness of the proposed control strategy.